Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3389/fncel.2023.1170251
|View full text |Cite
|
Sign up to set email alerts
|

Brain-derived neurotrophic factor contributes to neurogenesis after intracerebral hemorrhage: a rodent model and human study

Abstract: Background and purposeIntracerebral hemorrhage (ICH) enhances neurogenesis in the subventricular zone (SVZ); however, the mechanism is not fully understood. We investigated the role of brain-derived neurotrophic factor (BDNF) in post-ICH neurogenesis in a rodent model and in patients with ICH using cerebrospinal fluid (CSF).MethodsA rat model of ICH was constructed via stereotaxic injection of collagenase into the left striatum. Patients with ICH receiving an external ventricular drain were prospectively enrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…However, the microenvironmental changes that occur after pathological damage typically impede neurogenesis and tissue repair ( Ge et al, 2023 ), resulting in neurological deficits. Previous studies have primarily focused on illustrating the changes in NSCs located in the SVZ during ICH ( Lin et al, 2023 ). However, these findings are insufficient in explaining the cognitive impairment following ICH.…”
Section: Discussionmentioning
confidence: 99%
“…However, the microenvironmental changes that occur after pathological damage typically impede neurogenesis and tissue repair ( Ge et al, 2023 ), resulting in neurological deficits. Previous studies have primarily focused on illustrating the changes in NSCs located in the SVZ during ICH ( Lin et al, 2023 ). However, these findings are insufficient in explaining the cognitive impairment following ICH.…”
Section: Discussionmentioning
confidence: 99%
“…After ICH, microglia and macrophages produce NTFs, particularly neurotrophins, to initiate repair. Studies have shown that BDNF can reduce hematoma volume, promote neural regeneration, and improve behavioral outcomes in models [ 129 , 130 , 131 , 132 ]. Similarly, NGF has been found to reduce inflammation and improve neurological function in patients [ 133 , 134 ].…”
Section: Alcohol and Neuroinflammatory Mechanism Activated In Sbimentioning
confidence: 99%